Social inclusion and equality between men and women: A study of ambivalent sexism in the Roma population - Moreno López, Roberto; Ytarte, Rosa Mari; Venceslao Pueyo, Marta; Morales Calvo, Sonia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The objective of the research is focused on the study of the evolution of sexism as a cultural parameter in the Roma population whose people maintain recognition as an ethnic minority in Europe. The design selected for this study is descriptive. This study involves testing the reliability of the reduced version of the ambivalent sexism inventory (ASI; Glick and Fiske, 1996) scale among a representative group of the Roma population belonging to the city of Toledo. A representative sample of 44 people aged between 16 and 40 years was selected, with an average of 27.3. The results confirm the reliability of the scale and provide little differentiation and sex-disaggregated results. The responses on the items show a high degree of sexism among the participants. The obtained results give a better understanding of the scope of gender roles and, therefore, can help us to reorient interventions in the prevention of gender inequalities or early school dropouts among Roma girls.